Pengembangan E-LKPD Berbasis Realistic Mathematics Education Materi Persamaan dan Pertidaksamaan Linear Satu Variabel - Bimo Bimantoro; Sumargiyani Sumargiyani (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
Difficulties experienced by students in interpreting the concepts of One-Variable Linear Equations (OVLE) and One-Variable Linear Inequalities (OVLI), particularly in translating contextual problems into mathematical models, remain one of the challenges encountered in the learning process. This condition indicates the need for learning media capable of connecting mathematical concepts with students' real-life experiences. This study aimed to develop a Realistic Mathematics Education (RME)-based Electronic Student Worksheet (E-LKPD) on One-Variable Linear Equations and One-Variable Linear Inequalities for junior high school students and to describe its validity and practicality. The study employed a Research and Development approach by adopting the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The product was developed in digital form and evaluated through validation by subject matter experts and media experts before being implemented with students and teachers. The results of the expert validation indicated that the developed E-LKPD was valid. In addition, the results of the field trials showed that the E-LKPD was practical based on both students' responses and teachers' responses. The characteristics of RME in the E-LKPD were reflected through the presentation of contextual problems, mathematization activities, and interactive tasks that assisted students in relating everyday situations to mathematical concepts. Therefore, the developed RME-based E-LKPD met the criteria of validity and practicality and has the potential to serve as an alternative digital learning medium to support more meaningful mathematics learning.